Response of winter bird communities to environmental variables in riparian zones of cold region: a case study in Shenyang, Northeast of China - Wu, Chengrun; Dong, Yukuan; Liang, Zhipeng; Wang, Qiushi (Frontiers in Ecology and Evolution, 2025)
IntroductionLandscape changes resulting from urbanization have profound impacts on biodiversity, threatening the habitat of resident species. Birds are valuable research subjects because of their diversity, wide distribution, and particular sensitivity to environmental changes. Therefore, exploring the relationships between winter birds and environmental variables is essential for designing and managing green spaces during winter. However, the responses of the winter bird communities to environmental variables in cold regions remain unclear.MethodsIn this study, we investigated the winter bird community in the riparian zone of the Hun River in Shenyang. We selected 11 environmental variables of the riparian zone and conducted a principal component analysis to extract seven new components that represent environmental changes. Subsequently, we performed correlation and redundancy analyses on bird diversity indicators and environmental variables.ResultsThe results revealed that bird richness, Simpson’s diversity index and Shannon diversity index, was greater in the urban expansion area than in the urban core area. However, abundance was lower in the urban expansion area. Disturbance and built-up components were significantly associated with overall bird diversity, while disturbance, riparian, open vegetation, and suburban vegetation components were significantly linked to the diversity of resident and migratory birds. Birds in the urban expansion area exhibited greater sensitivity to environmental variables compared to those in the urban core area.DiscussionThis study recommend focusing on seasonal influence on birds’ resource use and urbanization level and bird species composition in riparian zones.